Harta Bersama Perspektif Syariah dan 'Adah (Kebiasaan): Penelitian - Muhammad Fadhil (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to analyze the differences and similarities between sharia (Islamic law) and customs in the context of joint property and analyze conflicts that may arise in the ownership and management of joint property, as well as efforts to resolve them based on the perspective of sharia and customs. This research was conducted using a qualitative method approach. This qualitative method uses literature study and comparative analysis methods to collect and analyze data. The results of this study show that sharia and customs have different approaches in regulating the issue of joint property. Sharia has a strong legal foundation based on the Quran and hadith, while adat is based on the traditions and culture of the community. Despite the differences, this study also found some similarities in the principles applied in both sharia and customs related to joint property. The implementation of this research is the importance of harmonization between sharia and customs in resolving joint property cases. There are challenges and conflicts that may arise, but efforts to reach a common understanding and balance between sharia and adat can help create the right solution. Cooperation between sharia institutions and stakeholders is needed to realize legal harmony that meets the needs of the community holistically.